Strategi Branding Digital untuk Meningkatkan Brand Awareness UMKM: Studi Kasus Nimet by Ais Food - Gladys Valerina Warouw; Regina Natania Kristanto; Richlauder Lamhot PP; Melly Sari Nova Br Tarigan; Rayhan Indarta R; Dzikra Ghaniya Ryalh; Muhammad Budiman; Tri Siwi Agustina Agustina (PASAI : Jurnal Pengabdian kepada Masyarakat, 2026)
NIMET by Ais Food is a culinary micro, small, and medium enterprise (MSME) operating in the city of Surabaya that faces various challenges in the areas of branding and digital marketing. This community assistance activity aims to improve business visibility through the optimization of brand identity and the utilization of digital platforms. The methods employed include direct interviews with the business owner using Probing Question techniques, the Funnel Method, and the 5W+1H approach. The assistance was carried out through three visits between March and May 2026 at the business location of Bu Aisyah, the owner of NIMET by Ais Food. Based on the results of observation and interviews, the main problems identified were inconsistent visual identity, the business not being registered on Google Maps, and suboptimal use of social media. As solutions, the team implemented a logo redesign, the creation of a product price list, packaging sticker design for the Cappuccino product, registration of the business location on Google Maps, and the creation of a TikTok account as a digital promotional channel. The results show that NIMET by Ais Food now has a more consistent and professional visual identity, a discoverable location on Google Maps, and an active TikTok account with authentic promotional content. This mentoring activity is expected to serve as a reference for developing digital marketing strategies for other culinary MSMEs.